A cross-sectional feasibility study of neurovascular ultrasound in Malawian adults with acute stroke-like syndrome. - Joseph Kamtchum-Tatuene; Henry C Mwandumba; Gloria Mwangalika Kachingwe; Laura J Bonnett; Noel Kayange; Tom Solomon; Laura A Benjamin (PLoS ONE, 2020)
Background In sub-Saharan Africa, there is a dearth of epidemiologic data on the burden of cerebral atherosclerosis. This is explained by the limited availability and the high cost of standard vascular imaging techniques. Neurovascular ultrasound is portable, cheaper and non-invasive and could, therefore, represent a reasonable alternative to fill this knowledge gap. We explored the feasibility of neurovascular ultrasound in Malawian adults with acute stroke-like syndrome to inform the design of future large stroke studies comparing its diagnostic performance to that of gold standard vascular imaging techniques in sub-Saharan Africa. Methods We enrolled consecutive patients diagnosed with acute stroke-like syndrome based on the World Health Organization definition. Clinical and demographic data were recorded, and a comprehensive neurovascular ultrasound was performed. Fisher's exact and Kruskal-Wallis tests were used to study the relationship between atherosclerosis and potential risk factors. Results Sixty-six patients were enrolled (mean age: 58.7 years). The frequency of extracranial atherosclerosis was 39.4% (n = 26, 95% CI: 28.6-52.2). There were 12 patients with abnormal carotid intima media thickness (18.2%, 95% CI: 9.8-29.6) and 14 patients with a carotid plaque (21.2%, 95% CI: 12.1-33.0). The frequency of intracranial atherosclerosis was 19.2% (95%CI: 6.6-39.4) in 26 patients with successful transcranial insonation. Hypertension (80.8 versus 52.5%, p = 0.03) and hypercholesterolemia (11.5 versus 0.0%, p = 0.05) were more prevalent in patients with extracranial atherosclerosis. Conclusions This study demonstrates the feasibility of neurovascular ultrasound to assess cervical arteries in adults with stroke-like syndrome in sub-Saharan Africa. There is a high rate of transcranial insonation failure in this setting, highlighting the need for echocontrast agents.